Bridging macro bibliometrics and micro molecular mechanisms: an integrated analysis of global aortic dissection research - Yunnan Hu; Yixie He; Fan Xu; Liangwan Chen (Frontiers in Cardiovascular Medicine, 2026)
Background Aortic dissection (AD) is a catastrophic cardiovascular emergency with high morbidity and mortality. Despite advances in diagnosis and treatment, its complex pathogenesis, optimal therapies, and postoperative complications remain major challenges. Although AD research has expanded substantially, quantitative analyses integrating global knowledge structures with molecular mechanisms remain limited. This study mapped the development, contributors, hotspots, and emerging frontiers of global AD research to support future investigation and clinical translation. Methods AD-related literature published from January 1, 2000, to December 31, 2025, was retrieved from the Web of Science Core Collection and Scopus. Excel, VOSviewer, CiteSpace, Scimago Graphica, and bibliometrix were used for bibliometric analyses, and a logistic growth model characterized publication trends. Single-cell RNA sequencing datasets GSE254132 and GSE213740 served as discovery and external-validation cohorts, respectively. Seurat, Harmony, donor-level pseudobulk differential expression, and exact donor-label permutation tests were applied. Differentially expressed genes were linked to target-specific PubMed trajectories to distinguish established AD genes from literature-sparse candidates. Results A total of 5,170 publications were included. Output accelerated after 2010 and reached 712 articles in 2025. China produced the most publications, whereas the United States had the highest citation count and strongest international collaboration. Four convergent frontiers emerged: endovascular therapy, inflammation and vascular-wall remodeling, candidate molecular markers, and machine-learning-based prognosis. In GSE254132, AD was associated with vascular smooth muscle cell remodeling and a higher proportion of SPP1⁺ remodeling macrophages. GSE213740 reproduced the direction of this remodeling program and showed a smaller increase in SPP1⁺ macrophages despite compositional differences. During 2000–2025, PubMed indexed 1,483 publications on angiopoietin-like 4 (ANGPTL4) and 240 on matrix metalloproteinase 19 (MMP19) across biomedical fields. Output increased by 49.9% and 43.5%, respectively, in 2021–2025 versus 2016–2020. Record-level screening identified only two original AD-relevant publications for each target. Conclusion This study maps the global structure and changing priorities of AD research and uses human single-cell data as a biological cross-check and candidate-prioritization layer. The combined evidence identifies ANGPTL4 and MMP19 as literature-sparse molecules that warrant mechanistic investigation, not as validated therapeutic targets. Independent cohorts and functional experiments are required before either molecule can be assigned diagnostic or therapeutic value.